Exploring The Effectiveness of Artificial Intelligence in Detecting Malware and Improving Cybersecurity in Computer Networks - Komarudin Komarudin; Isma Elan Maulani; Tedi Herdianto; Medika Oga Laksana; Dwi Febri Syawaludin (Green Publisher Indonesia, 2023)
Malware, in particular, has been identified as a major cy-bersecurity challenge due to its ability to infiltrate computer networks, steal sensi-tive data, and cause major damage to computer systems. The purpose of this study was to explore the effectiveness of artificial in-telligence in detecting malware and improving cybersecurity in computer net-works. Success rate in detecting and preventing malware attacks on computer networks using AI-based methods. The time it takes to detect and prevent malware attacks on computer net-works using AI-based cyber protection methods. Furthermore, the selection of two types of malware that are often found on computer networks, namely Trojans and Worms, and data sampling was then test-ed on a simulation system. In this study, three different AI techniques were applied, namely Support Vector Machine, Neural Network , and Decision Tree to detect malware on computer networks.